The Legal Regulation of Foreign Workers According to the Saudi Labor Law - Arjwan Abdullah Al-Qarni (International Journal of Law Research and Studies, 2025)
This study aims to define the concept of the foreign worker and identify the conditions and regulations governing their employment under the Saudi Labor Law. It also examines the rights guaranteed by the system to foreign workers, explores how the law regulates their ability to move to another job or change professions, and clarifies the obligations imposed on them by the relevant legal provisions. Using the analytical method, the study analyzes the provisions of the Saudi Labor Law along with other related legal texts to outline the legal framework for the rights and obligations of foreign workers in Saudi Arabia. The study arrived at several key findings, including that the Saudi Labor Law does not explicitly define the foreign worker but rather provides a general definition of workers. Foreign workers enjoy both general and specific rights that ensure fair treatment, including the ability to move from one employer to another under specific regulations, as well as the right to change professions through established legal procedures. Additionally, the law imposes various obligations on foreign workers, such as performing their duties in accordance with professional standards, maintaining the employer’s property, preserving confidentiality regarding workplace secrets, and refraining from competing with the employer after the termination of their contract. Furthermore, the study presents several recommendations, including the necessity of explicitly defining the foreign worker within the Saudi Labor Law, conducting periodic reviews of the list of professions prohibited for foreign workers, and enhancing regulatory measures to ensure compliance with legal obligations. These steps contribute to establishing a balanced and stable work environment in the Kingdom of Saudi Arabia.